Landslide Hazard Assessment Model for Slope Stability Analysis - De Santis, Giulia; Egidi, Nadaniela; Giacomini, Josephin; Gioia, Eleonora; Maponi, Pierluigi; Spadoni, Lorenza (Journal of Advances in Applied & Computational Mathematics, 2023)
Soil moisture dynamics is a complex phenomenon that depends on the atmospheric conditions, the geomorphological characteristics of the region under study, and the corresponding land use. It can be formally described by a diffusion model based on Darcy’s law and the law of mass continuity. In this work, the obtained numerical solution of the hydrological model has been exploited to evaluate the soil moisture in a given region and build a risk map for the slope stability of this region. More in detail, the infinite slope model from slope stability analysis has been used for evaluating the safety factor and constructing the corresponding quantitative hazard maps. Some results of the proposed method applied to a real case study are shown and discussed.